Study of Wear Behavior of Zircon Sand Reinforced Aluminium Matrix Composites - Panwar, Ranvir Singh (My University, 2014)
The present work deals with the development and characterization of zircon sand reinforced LM13 aluminum alloy composites. The entire work in this thesis is presented in six chapters. In the first chapter general introduction to particle reinforced composite is given. A summary of discontinuous reinforced aluminum matrix composite along with different fabrication processes of aluminum matrix composites are also described in this chapter. The main factors affecting the mechanical properties of the composites along with brief introduction to different types of wear is also given at the end of the chapter. Chapter 2 describes the development of discontinuous reinforced aluminum matrix composites (DRAMCs) by many researchers using different fabrication techniques and their study based on wear behavior is discussed in this chapter. As our work is based on the stir casting process, hence the main focus in this chapter is on the development of DRAMCs by stir casting process and study their physical properties especially wear resistance of the composites. The last section of this chapter presents the gaps in the study so far with aims and plan of the work of the thesis. Chapter 3 describes about experimental procedure followed in the present work. Detailed procedure to develop the DRAMCs and their characterizations is given in this chapter. Different characterization techniques such as X- ray diffraction (XRD), Optical microscopy, Scanning electron microscopy (SEM), Energy dispersive spectroscopy (EDS), Rockwell hardness testing, Vickers hardness testing and wear testing with pin-ondisc machine along with their operating parameters are also discussed. A flow chart of the methodology used is also given in this chapter. Chapter 4 deals with results and discussions on as developed composites reinforced with single size reinforcement. The effect of variation in amount and particle size of the reinforced zircon sand particles in the LM13 alloy matrix is discussed. On the basis of the results obtained by XRD, optical microscope, SEM, hardness testing and pin-on-disc wear test, a possible mechanism for wear is discussed. In this chapter, surface morphology of the single size particles reinforced composites were studied with the help of optical microscope to observe the distribution of the particles in the matrix. Both bulk and microhardness were measured for each composite with Rockwell and vicker’s xviii hardness testing machine. All composites were tested with pin- on– disc machine for dry sliding wear test at different load and different temperature conditions. Wear tracks and wear debris were analyzed by using SEM. In Chapter 5, results obtained from the composites reinforced with dual size particles (coarse and fine) are presented. The role of different ratios of the coarse and fine size particles in the matrix on the wear behavior have been studied with variation in the applied load and temperatures. However, on the basis of results, worn surfaces and wear debris of the DSR-15 composite (containing total 15 wt.% of dual particle size reinforcement) collected after the wear test at different conditions were analyzed under SEM. Chapter 6 describes the conclusion of the entire work done in the present investigation along with the future scope. The present work shows a good distribution of the zircon sand particles in LM13 alloy matrix developed by stir casting process. XRD data shows the presence of zircon sand particles as well as new phase developed during the casting process. Uniform distribution and bonding of zircon sand particles with the matrix was observed. It was found that hardness of the base alloy was improved with increasing the amount of zircon sand particles in the matrix. However, with decreasing the particle size hardness of the composites was increased significantly. Ratios of the coarse and fine size particles in the matrix (dual size reinforced composites) shows better hardness in comparison to the single size reinforced composites. Wear test of all the developed composites were done at different testing conditions with varying loads and temperatures. It was observed that wear resistance of the base alloy was improved with increasing the amount as well as decreasing the size of the reinforced particles. However, wear rate of the composites increases with increasing the applied load. Ambient temperature also plays an important role on the wear behavior of the composites. Formation of oxide layers at high temperature affects the wear rate significantly for all loading conditions. However, DSR composites shows better wear resistance in comparison to the SSR composites at all testing conditions.
PHD, SPMS
Keywords: Metal Matrix Composite; Wear; Zircon sand; Stir Casting